2019
DOI: 10.1002/jctb.6082
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The fabrication of magnetic recyclable nitrogen‐doped titanium dioxide/calcium ferrite/diatomite heterojunction nanocomposite for improved visible‐light‐driven degradation of tetracycline

Abstract: BACKGROUND: Powdery photocatalysts have long been studied in various aspects, yet their low recovery in suspension systems remains the bottleneck hindering their practical application. An alternative method to overcome this shortcoming is to develop magnetic recyclable ferrite-based hybrid photocatalysts. In this work, we prepared a nitrogen (N)-doped titania (TiO 2 )/calcium ferrite (CaFe 2 O 4 )/diatomite (Dt) (N-TCD) ternary hybrid via the sol-gel method. The physicochemical properties of various hybrid cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Such behavior is confirmed by studying the degradation pathway of TC; it was found that the TC intermediates match those that formed through radical driven reactions undergoing in the first step demethylation and hydroxylation. The second step considered the removal of functional groups (amino, hydroxyl, and methyl) and further ring opening reactions that are mainly mediated by photogenerated h + , yielding small fragments that were eventually mineralized [44]. Such a pathway confirmed the dual role of photogenerated h + , as a promotor •OH generation and as sites for the direct oxidation of adsorbed organics.…”
Section: Tio 2 /Fe 2 Omentioning
confidence: 90%
See 3 more Smart Citations
“…Such behavior is confirmed by studying the degradation pathway of TC; it was found that the TC intermediates match those that formed through radical driven reactions undergoing in the first step demethylation and hydroxylation. The second step considered the removal of functional groups (amino, hydroxyl, and methyl) and further ring opening reactions that are mainly mediated by photogenerated h + , yielding small fragments that were eventually mineralized [44]. Such a pathway confirmed the dual role of photogenerated h + , as a promotor •OH generation and as sites for the direct oxidation of adsorbed organics.…”
Section: Tio 2 /Fe 2 Omentioning
confidence: 90%
“…Hence, the contribution of H 2 O 2 in such a system can be described through restraining e − /h + recombination and increasing HO• generation in the system, as in Equation 1 [42,43]. Spinel ferrites band positions match TiO 2 , thus possessing compatibility to form a heterojunction (Type II Heterojunction) [44][45][46][47].…”
Section: Tio 2 /Fe 2 Omentioning
confidence: 99%
See 2 more Smart Citations